A importância do parque verde urbano na região administrativa do Gama: funções sociais - PINA, Érida Machado Barbosa de (2024)
Urban parks are green areas for collective use by civil society. They are used for the leisure of a population, including contact with the environment and for cultural, physical and sports activities. The study aims to present and analyze the social functions of the Urban Park in the Administrative Region of Gama, in the Federal District, one of the few green spaces available for leisure and sports in the region. The research, with a quantitative approach and using the SOPARC (System for Observing Play and Recreation in Communities) application, revealed that most park visitors are adults (56.35%), followed by adolescents (28.37%), elderly people (13.54%) and children (1.73%). There was a predominance of male visitors (73.13%) over female visitors (26.87%). Soccer fields, especially those with synthetic grass, were the most frequented places, representing 56.59% of the total users observed. The jogging track also stood out, with 19.57% of the total attendance, being used mainly for walking and running. Most adults (40%) engaged in vigorous physical activities, such as soccer and running, while 59% engaged in moderate activities, such as walking. 67% of adolescents engaged in vigorous activities, and 31% in moderate activities. 63% of children engaged in vigorous activities, and 34% in moderate activities. Most elderly individuals (77%) engaged in moderate activities, such as walking, and 22% in vigorous activities. Analysis of user frequency over the months demonstrated significant variation, with a peak in December (1205 visitors) and drops in January and February (722 and 671 visitors, respectively), possibly due to the rainy season. The survey data reveal that the Gama Ecological Park is an important space for practicing physical and leisure activities, especially for adults and male adolescents. However, the low frequency of other groups, such as children, elderly individuals and women, points to the need for actions that promote a more inclusive and diverse use of the park. The creation of specific spaces and activities for these audiences, in addition to the revitalization of less frequented areas, can help the park meet the needs of the entire community and consolidate itself as a space for promoting health, leisure and well-being for all.